Pelatihan Penulisan Position Paper Model United Nation Bagi Mahasiswa Hubungan Internasional Universitas Tanjungpura - Alunaza, Hardi (Journal of Community Development, 2024)
This service community is based on the obstacles faced by international relations students in West Kalimantan who do not have good skills in writing position papers. Another obstacle encountered is that many students do not like reading international news or journals, so they are not confident in following the United Nation model.However, students should have adequate skills in scientific writing, communication skills in English, public speaking, analytical skills and critical thinking.The aim of this activity is helping to stimulate students to have the courage to write and practice taking part in MUN, and to get used to conveying ideas and arguments in public. This activity was carried out in September 2022 with educational material regarding position papers, questions and answers, documentation and reporting. After participating in training activities, students have increased understanding in writing topic background, past international action, country policy, and possible solutions. That can be seen from the relevance of the topic, sharpness of arguments, appropriateness of structure, use of appropriate language, and consistency in writing. Students also understand examples of position papers on various topics such as politics, economics, social and culture.